Profunda femoris artery injury caused by lesser trochanter fragment in intertrochanteric fracture: A case report - Chatchanin Mayurasakorn; Vajara Phiphobmongkol; Wasupong Sridermma; Suthorn Bavonratanavech (Trauma Case Reports, 2018)
Vascular injuries following intertrochanteric fracture have been sporadically reported. Despite its rare occurrence, this complication can be potentially life and limb threatening. The authors report an unusual presentation of false aneurysm of profunda femoris artery following an intertrochanteric fracture with marked displacement of lesser trochanter fragment. The patient presented with thigh swelling and unexplainable dropped hematocrit. Surgical exploration and vascular repair were done. It is essential for the surgeon to be aware of possible associated vascular injuries in intertrochanteric fracture, particularly in fracture with lesser trochanter fragment.